Ultra high‐frequency ultrasound: New capabilities for nail anatomy exploration. Issue 1 (12th July 2016) - Berritto, Daniela; Iacobellis, Francesca; Rossi, Claudia; Reginelli, Alfonso; Cappabianca, Salvatore; Grassi, Roberto
Abstract: Recent development of ultra high‐resolution ultrasound systems, with frequencies as high as 70 MHz and capability resolution as fine as 30 μm, could permit new diagnostic applications to small parts. A variety of superficial targets within the first 1 cm of the skin surface could be imaged, including dermatological applications such as assessment of skin layers, hair follicles and the nail unit. Nail disorders are frequent but they are diagnosed mainly based on clinical examination; although biopsies and scrapings can provide clinically significant information, most patients do not perceive biopsies positively. To image the skin layer and annexes is often difficult with conventional ultrasound but, because of anatomical details obtained with the newest systems, this method holds great promise for addressing important biomedical applications offering unique advantages over the existing non‐invasive imaging modalities. This will enable physicians to assess and manage the conditions involving the nails of a large and growing segment of the population in a better way.